2023
DOI: 10.1213/ane.0000000000006418
|View full text |Cite
|
Sign up to set email alerts
|

Transnasal Videoendoscopy for Preoperative Airway Risk Stratification: Development and Validation of a Multivariable Risk Prediction Model

Abstract: BACKGROUND: Transnasal flexible videoendoscopy (TVE) of the larynx is a standard of care for the detection and staging of pharyngolaryngeal lesions in otorhinolaryngology. Patients frequently present with existing TVE examinations before anesthesia. Although these patients are considered high risk, the diagnostic value of TVE for airway risk stratification is currently unknown. How can captured images or videos be used for anesthesia planning, and which lesions are most concerning? This study aimed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 38 publications
0
18
1
Order By: Relevance
“…However, convincing evidence on the usefulness of a preoperative endoscopy in the general population requiring general anesthesia is lacking. Still, there has been increasing interest in the matter as fiberoptic technology has become available, and a few studies have shown that transnasal fiberoptic airway assessments could improve the predictability of routine airway examinations regarding conventional laryngoscopy or videolaryngoscopy [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, convincing evidence on the usefulness of a preoperative endoscopy in the general population requiring general anesthesia is lacking. Still, there has been increasing interest in the matter as fiberoptic technology has become available, and a few studies have shown that transnasal fiberoptic airway assessments could improve the predictability of routine airway examinations regarding conventional laryngoscopy or videolaryngoscopy [ 29 , 30 , 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Flexible rhinolaryngoscopy is not used to its full potential in anesthesia, intensive care, or emergency departments, despite recommendations in guidelines to consider it in patients with possible airway pathology of a tumoral, inflammatory, or traumatic nature that could preclude mask ventilation and impede the placement of a supraglottic device or an intubating tube [ 10 , 28 ]. Its utility in assessing anatomically difficult airways is yet to be determined, but a few studies have shown its benefit [ 29 , 30 ]. As technology progresses, this device will become handier, more affordable, and provide sharper images, and patients rate it as having good procedure tolerability.…”
Section: Discussionmentioning
confidence: 99%
“… 11 13 Only patients with indicators for difficult tracheal intubation, such as a SARI ≥ 4 points, Wilson score ≥ 2 points, a positive ULBT, relevant pharyngolaryngeal lesions, reported previous difficult tracheal intubations (e.g., anesthesia alert card or a videolaryngoscopic intubation and difficult airway classification [VIDIAC] score ≥ 2), or a combination of these factors were considered eligible for study inclusion. 5 , 11 , 13 16 Furthermore, patients were checked for indicators for awake tracheal intubation using a previously recommended decision-making tool taking predictors for difficult tracheal intubation, suspected difficult facemask and/or supraglottic-airway ventilation, physiologic issues such as apnea intolerance, risk for aspiration and hemodynamic instability, and contextual issues into account. 2 Patients that qualified for awake tracheal intubation or required a nasotracheal intubation, special tubes such as laser or microlaryngoscopy tubes, rapid-sequence induction, or had loose teeth were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Adults who presented at our Anesthesia Preassessment Clinic before elective ear, nose and throat or oral and maxillofacial surgery between April 1, 2019 and April 3, 2020 were assessed for eligibility. All patients received a structured preoperative airway risk assessment in accordance with standards laid out by the Department of Anesthesiology that comprises clinical history and physical examinations [such as the upper lip bite test, the simplified airway risk index and flexible nasendoscopy ( 28 , 29 ) if appropriate] ( 30 , 31 ). Details are reported elsewhere ( 11 ).…”
Section: Methodsmentioning
confidence: 99%